Hubungan Kadar HB dan Junk Food dengan Kejadian Disminorea Pada Remaja Putri - Herman, Hernianti; Dewanti, Ritma; Ishak, Syamsopyan; Rate, Suherman; Dewi, Apiska Prima (Jurnal Ilmu Kebidanan, 2024)
Background; Dysmenorrhea is a problem that occurs in women of reproductive age which has an impact on reducing women's productivity and quality of life, such as absence from school, activity restrictions, decreased academic performance, sleep disorders, mood disorders. Purpose; This research was to determine the relationship between hemoglobin levels and junk food with the incidence of dysmenorrhea in female girls. Methods: ; This research was conducted at STIKES Adila Bandar Lampung with 30 female respondents from the Undergraduate Nutrition Study Program. Data collection was carried out by checking hemoglobin levels, frequency of consumption of junk food and desminorrhea levels. Results: Based on the Pearson Correlation test, the research results show hemoglobin levels with a p value of 0.442 > 0.05 with a Pearson correlation value of -0.146 and the junk food variable with a p value of 0.012 < 0.05 with a Pearson correlation value of 0.451. Conclusion So it can be concluded that there is no clear linear relationship between hemoglobin levels and the incidence of dysmenorrhea, but there is a positive linear correlation between consumption of junk food and the incidence of dysmenorrhea.